Voluntary abortion in Cuba: advances and challenges - Esquenazi Borrego, Arelys (Argumentum, 2023)
Cuba was the first country in Latin America and the Caribbean to decriminalise abortion and create regulations allowing it to be performed legally, safely and free of charge. This article analyses the current situation of voluntary abortion in Cuba. The main conclusion is that, despite the advances achieved over the more than six decades of the Revolution, there are still several challenges from a legal and social point of view. In addition to legal issues, other challenges relate to the improvement of medical procedures, and more effective and comprehensive programmes and methods associated, for example, with sex education and contraception. The research methodology was triangulated bibliographical research, analysis of official documents and descriptive statistics.Keywords: Voluntary abortion. Sexual and reproductive rights. Reproductive justice. Women. Cuba.